Applications of group theory in physics and chemistry - 596254 Fong, Wan Heng; Nor Haniza Sarmin; Fakulti Sains (2003)
Project Paper (Sarjana Muda Sains serta Pendidikan (Matematik)) - Universiti Teknologi Malaysia, 2003